Численное моделирование теплообмена в топке водотрубного парового котла ДЕ-10/14 при различной тепловой нагрузке - Редько, А. А.; Давиденко, А. В.; Павловский, С. В.; Куликова, Н. В.; Редько, И. А. (НТУ "ХПИ", 2016)
Наведено результати чисельного дослідження процесів теплообміну в топці парового котла ДЕ-10/14 з пальником ГМГ. Визначено структуру факела, наявність зворотних струмів і течій поблизу теплообмінних поверхонь топки котла. Показані поля розподілу температури, щільності променистого теплового потоку в топковому об'ємі при різних експлуатаційних режимах (100, 50 і 15 % паропродуктивності котла).

The results of numerical studies of heat transfer processes in a furnace boiler DE-10/14 with a burner of HMG given. Determined the structure of the torch, the presence of reverse currents and currents near the heat exchange surfaces of the boiler furnace. Showing field distribution of temperature, density of the radiant heat flow in the combustion volume at different operating conditions (100, 50 and 15 % of steam boiler).
Numerical modeling of heat transfer in the furnace water tube steam boilers DE-10/14 at different heat capacity
Keywords: закон Фурье; температурное поле; сжигание газа; тепломассообмен; уравнения Навье-Стокса